FRI0186 Impact of Concomitant Methotrexate Dose on the Efficacy and Safety of Sarilumab for Treatment of Moderate-to-Severe Rheumatoid Arthritis: The Mobility Study. (9th June 2015) - Huizinga, T.W.J.; Yazici, Y.; Thompson, D.; Decktor, D.L.; Fan, C.; Fleischmann, R.
Abstract : Background: Methotrexate (MTX) is the most commonly used conventional synthetic DMARD (csDMARD) for the treatment of rheumatoid arthritis (RA). In the phase 3 MOBILITY study (NCT01061736 ), 1 of sarilumab in inadequate responders to MTX, MTX was continued at the dose prescribed at screening, which was assumed to be the maximally tolerated dose. This sub-analysis evaluates whether the different doses of MTX, in association with sarilumab, had an effect on efficacy or safety outcomes in MOBILITY. Objectives: To explore the relationship of MTX dose on the efficacy or safety of sarilumab in the treatment of active RA in MTX-IR patients. Methods: The MOBILITY study design and methods have been reported. 2 Patients were required to be on a stable dose of MTX of 10–25 mg/wk for at least 6 weeks, except for Asian-Pacific region patients (6–25 mg/wk) prior to enrolment and to maintain this dose throughout the trial. A sufficient number of subjects with doses of 7.5-25 mg/wk were included: 11 (0.92%) patients were excluded from the analysis due to small numbers receiving doses of <7.5 and >25mg/wk. The relationship between efficacy and safety outcomes for sarilumab and MTX was assessed by appropriate regression models (logistic or generalized linear) in this post hoc analysis. Results: 1186 patients were included. For each dose group in each treatment arm we computed proportions of ACR20 responders at Wk 24 and 52; no apparent difference in achieving an ACR20 response was observed with increasing MTX dose in any treatment group (Figure ). A logistic regression assessment confirms this observation: for sarilumab 150 mg and 200 mg. Based on mean change from baseline in HAQ-DI at Wk 24, no apparent relationship with MTX dose was observed. A linear regression model assessment provides confirmation of the results. There was no statistical difference in mean HAQ-DI change from baseline based on MTX dose in the Pbo, sarilumab 150 mg or sarilumab 200 mg groups. Similar findings were observed for changes from baseline for DAS28-CRP, FACIT-Fatigue, and mTSS (change and progression). There was no association of the incidence of treatment-emergent adverse events (AE), serious AEs and changes in ALT, neutrophil counts and lipids with increasing MTX doses. Conclusions: In this post hoc analysis, within the sarilumab 150 mg or sarilumab 200 mg dose groups, efficacy or safety was similar across concomitant MTX doses. References: Genovese M et al. Abstr. No. EULAR14-SCIE-3001 presented at EULAR 2014, Paris, France Kavanaugh A et al. Abstr. No. 2824 presented at ACR 2014, Boston, MA, USA Acknowledgements: The study was sponsored by Sanofi and Regeneron Pharmaceuticals Inc. Editorial support was provided by Diane Davies of Envision Scientific Solutions and was funded by Sanofi and Regeneron Pharmaceuticals Inc. Disclosure of Interest: T. Huizinga Consultant for: Merck, UCB, BMS, Biotest AG, Pfizer, Novartis, Roche, Sanofi, Abbott, Crescendo Bioscience, Nycomed, Boeringher Ingelheim, Takeda, Zydus, and Eli Lilly, Y. Yazici Shareholder of: Samumed, Grant/research support from: BMS, Celgene, Genentech, Consultant for: BMS, Celgene, Employee of: Samumed, D. Thompson Shareholder of: Regeneron, Employee of: Regeneron, D. Decktor Shareholder of: Johnson & Johnson, Employee of: Regeneron, C. Fan Shareholder of: Sanofi, Employee of: Sanofi, R. Fleischmann Grant/research support from: AbbVie, Amgen, Ardea, AstraZeneca, BMS, Celgene, GSK, Janssen, Eli Lilly, Merck, Pfizer, Resolve, Roche, Sanofi, UCB, Consultant for: AbbVie, Akros, Amgen, Antares, Ardea, AstraZeneca, Augurex, BMS, Celgene, Covagen, Five Prime, GSK, Iroko, Janssen, Eli Lilly, McNeil, Merck, Pfizer, Plexxicon, Resolve, Roche, Sanofi, Teva, UCB, Vertex